South Africa's capability to regulate and enforce the sale of digital goods - Stockigt, David Henry (University of the Witwatersrand, Johannesburg, 2023)
There are several challenges to regulating digital goods in South Africa. Firstly, the classification of digital goods can be found in the Films and Publication Amendment Act (FPAA), which seeks to bring the Films and Publications Act in line with new technologies and digital goods. The changes made within the FPAA raise other issues and questions of who is bound to the FPAA regulations, whether it only applies to publishers in South Africa and whether the regulations will be binding on individual publishers. Secondly, copyright enforcement has become more complex as the ability to replicate and reproduce copyright protected works has become easier. The Copyright Amendment Act (CAA) now offers greater protection of copyrighted works in the art, music, film, and video game industries through royalty agreements, allowing a copyright infringer to escape liability by paying an agreed amount for the use of the digital goods. Finally, the sale of a non-physical, digital good is governed by the Consumer Protection Act (CPA); it only provides general protections when entering into end-user licence agreements. Access to the digital good will find protection under the traditional law of contract principles. South Africa has made great progress in regulating the sale of digital goods however, many gaps remain within South Africa's law. Drawing from the analysis of foreign jurisdictions, such as the United States of America (USA) and the European Union (EU). The USA, unlike South Africa, has created specific laws to govern problems that directly result from the increase in the sale of digital goods. The USA has focused their efforts on regulating password sharing, the legal principle of first sale through the Digital Millennium Copyright Act and the Computer Fraud and Abuse Act. Finally, the USA has also allowed for specific copyright protection within the video game industry, protection that is not available in South Africa. On the other hand, the EU offers more generalised protection as the EU's Copyright provides broad solutions instead of individual laws addressing individual issues. The EU’s solutions include a strike system and the transfer of copyright infringement liability to the providers of the infringing material, allowing for adequate and efficient enforcement of copyright protections across multiple jurisdictions within the EU. South Africa would need to consider creating regulations that address live streaming, increasing video game copyright protection, and implementing the strike action through newly focused regulations rather than existing film and copyrights laws. By extending existing liability regulations to include those who provide access to the infringing material, it would enhance and encourage more well-rounded and sufficient protections in South Africa
A research report submitted in partial fulfillment of the requirements for the degree of Master of Laws by Coursework and Research Report at the University of the Witwatersrand, Johannesburg, 2023
Keywords: Non-fungible token; Digital goods; Copyright; Digital millennium copyright act; USA; EU Copyright directive; Video game la; Films and publication amendment act; UCTD; SDG-9: Industry, innovation and infrastructure